Corporation tax - Beattie, C.N; Wisely, J.C. (London : Butterworths, 1966)
The book deals not only with corporation tax but also with income tax and surtax liabilities of a company and its shareholders.
"With accountancy examples by J.C. Wisely"
Includes index.
obn 23/01/2019
Loans
Keywords: Corporations--Taxation.; Great Britain